(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Review of the book Balé Teatro Guaíra: 52 years of a history of dance in Paraná, written by Cristiane Wosniak. the work is a historical record that contains, among impressively vivid and clear images, testimonies, trajectories, curiosities and perspectives related to the main pillar of dance culture in Paraná. Transiting between past, present and future, the author presents us with almost four hundred pages, a detailed work that stitches education, body and memory; an engaging plot that will surely awaken in the reader his dancing verve.